2007
DOI: 10.1093/ndt/gfm762
|View full text |Cite
|
Sign up to set email alerts
|

The combined effect of pre-transplant triglyceride levels and the type of calcineurin inhibitor in predicting the risk of new onset diabetes after renal transplantation

Abstract: Pre-transplant hypertriglyceridemia was a risk factor for NODAT only in recipients treated with Tacro; it highlights the importance of pre-transplant insulin resistance in the pathogenesis of NODAT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
63
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 19 publications
7
63
0
Order By: Relevance
“…Interestingly, suppression of calcineurin activity improves insulin sensitivity in normoglycemic human subjects but exacerbates insulin resistance in diabetics (Ozbay et al, 2012; Porrini et al, 2008), supporting our observation that the therapeutic window for calcineurin intervention is in normoglycemic 5MO, but not older, insulin resistant Tg2576 (Figure 2). These observations may reveal the AD equivalent of the prediabetes state (De Felice and Ferreira, 2014) where elevated glucose, in the absence of overt insulin dyshomeostasis, can increase the risk of cognitive decline (Kerti et al, 2013).…”
Section: Therapeutic Opportunitiessupporting
confidence: 78%
“…Interestingly, suppression of calcineurin activity improves insulin sensitivity in normoglycemic human subjects but exacerbates insulin resistance in diabetics (Ozbay et al, 2012; Porrini et al, 2008), supporting our observation that the therapeutic window for calcineurin intervention is in normoglycemic 5MO, but not older, insulin resistant Tg2576 (Figure 2). These observations may reveal the AD equivalent of the prediabetes state (De Felice and Ferreira, 2014) where elevated glucose, in the absence of overt insulin dyshomeostasis, can increase the risk of cognitive decline (Kerti et al, 2013).…”
Section: Therapeutic Opportunitiessupporting
confidence: 78%
“…Israni et al (26) found posttransplant metabolic syndrome independently associated with subsequent risk of PTDM. When occurring pretransplantation, the metabolic syndrome (27) and its components such as pretransplant hypertriglyceridemia and BMI (28), as well as prediabetes (17) have predicted increased risk for PTDM. Specifically pretransplantation insulin resistance, putatively the underlying pathophysiology of metabolic syndrome, was found to be a risk factor for PTDM (7).…”
Section: Recommendation 4: Identify Patients At Risk For Ptdmmentioning
confidence: 99%
“…9,1519 The prevalence of and risk factors for diabetes in patients with earlier CKD stages (estimated glomerular filtration rate [eGFR] >60 mL/min/1.73 m 2 ) have not been evaluated previously in large studies. The most commonly used equation to estimate GFR is the Modification of Diet in Renal Disease (MDRD) Study equation.…”
mentioning
confidence: 99%